Cyclodialysis Cleft Associated with Kahook Dual Blade Goniotomy - Shue, Ann (J Curr Glaucoma Pract, 2019)
AIM: The aim of this study is to report cyclodialysis cleft creation during Kahook dual blade (KDB) goniotomy. BACKGROUND: No known reports of cyclodialysis clefts have been published to the authors’ knowledge after KDB goniotomy. CASE DESCRIPTION: A 55-year-old myopic male with primary open angle glaucoma in both eyes (OU) underwent routine cataract extraction and intraocular lens implant with KDB goniotomy in the right eye (OD). Preoperative intraocular pressures (IOP) OD were in the low 20 mm Hg range on timolol and bimatoprost. Postoperative IOP was 4 mm Hg, with a moderate depth anterior chamber. Gonioscopy was slit in all quadrants, with no structures visible, and no improvement on indentation. Mild macular choroidal folds were present OD. Ultrasound biomicroscopy (UBM) revealed an area of supraciliary fluid. Anterior chamber reformation with viscoelastic was performed and repeat gonioscopy revealed a cyclodialysis cleft from 2:00 to 3:00. Treatment with multiple sessions of argon laser photocoagulation successfully closed the cleft. CONCLUSION: KDB goniotomy may be complicated by cyclodialysis cleft formation and hypotony maculopathy. Visualization of a cleft on gonioscopy may require anterior chamber reformation. CLINICAL SIGNIFICANCE: With an increasing use of KDB for goniotomy, previously unreported complications may arise including cyclodialysis cleft and resultant hypotony maculopathy. Because cleft following KDB goniotomy is rare, suspicion may be low and diagnosis could be delayed in the setting of postoperative hypotony with closed angles. HOW TO CITE THIS ARTICLE: Shue A, Levine RM, et al. Cyclodialysis Cleft Associated with Kahook Dual Blade Goniotomy. J Curr Glaucoma Pract 2019;13(2):74–76.